2012
DOI: 10.1111/j.1540-5915.2012.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐Loop Supply Chains: A Critical Review, and Future Research*

Abstract: In this article, I present a review and tutorial of the literature on closed-loop supply chains, which are supply chains where, in addition to typical forward flows, there are reverse flows of used products (postconsumer use) back to manufacturers. Examples include supply chains with consumer returns, leasing options, and end-of-use returns with remanufacturing. I classify the literature in terms of strategic, tactical, and operational issues, but I focus on strategic issues (such as when should an original eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
324
2
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(344 citation statements)
references
References 94 publications
3
324
2
15
Order By: Relevance
“…Additionally, a close collaboration with a recommerce provider during this project yielded new insights into this fast developing industry. Thus, our research approach addresses the needs identified by Souza (2013) and Guide and Wassenhove (2009) as we consider a novel practice-driven problem setting and provide empirical results from an actual data set from the recommerce industry.…”
Section: Literaturementioning
confidence: 99%
“…Additionally, a close collaboration with a recommerce provider during this project yielded new insights into this fast developing industry. Thus, our research approach addresses the needs identified by Souza (2013) and Guide and Wassenhove (2009) as we consider a novel practice-driven problem setting and provide empirical results from an actual data set from the recommerce industry.…”
Section: Literaturementioning
confidence: 99%
“…There are contributions in the other streams noted above that intersect with the CLSC literature through a focus on reuse, remanufacturing, and/or recycling (e.g., for sustainable technology choice work that intersects with CLSC, see Debo et al 2005; for sustainable product design work that intersects with CLSC, see Plambeck and Wang 2009, Atasu and Subramanian 2012, and Subramanian et al 2013. Souza (2013) provides a thorough tutorial and review of the closed-loop supply chain literature, whereas Guide and Van Wassenhove (2009) describe the stream's evolution.…”
Section: Closed-loop Supply Chainmentioning
confidence: 99%
“…From social concerns about 3R (Reduce-ReuseRecycle) activity worldwide, it is urgently-needed to construct a new supply chain management which incorporates reverse chains/logistics into traditional forward chains/logistics (Guide and Wassenhove, 2009;Jayant et al, 2012;Souza, 2013;Govindan et al, 2014;Stindt and Sahamie, 2014;Schenkel et al, 2015;Radhi andZhang, 2016, Cannella et al, 2016). The traditional forward chains/logistics consist of the flows from procurement of new materials through production of new products to selling them.…”
Section: Introductionmentioning
confidence: 99%
“…The reverse chains/logistics are composed of the flows from collection of used products through recycling parts from the used products to reuse the recycled parts. Also, a supply chain which organizes the forward chains and the reverse chains has been called a closed-loop supply chain, a reverse supply chain, or a green supply chain (GSC) (Guide and Wassenhove, 2009;Souza, 2013;Govindan et al, 2014;Stindt and Sahamie, 2014;Bhattacharya and Kaur, 2015;Gurtu et al, 2015). A supply chain which is considered in this paper is called GSC in terms of greening effort/initiatives (Swami and Shah, 2013;Ghosh and Shah, 2015) in promoting collection activity of used products and remanufacturing activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation